ANALISIS PENERAPAN AKAD MURABAHAH PADA PEMBIAYAAN KREDIT USAHA RAKYAT (KUR) DI BANK SYARIAH INDONESIA KC PATI SUDIRMAN - Riska Istiyani; Ayunda Putri Nilasari (Mount Hope Economic Global Journal, 2025)
This study aims to determine how the implementation of the murabahah contract in KUR financing at BSI KC Pati Sudirman. This study uses a qualitative approach by conducting a comprehensive data analysis on a problem. The sources of this study are primary data and secondary data obtained from interviews, observations, and documentation. The results of the study that have been conducted indicate that the implementation of the murabahah contract in KUR financing at BSI KC Pati Sudirman is carried out with two contracts, namely the wakalah contract first, after carrying out the wakalah contract then carrying out the murabahah contract. This study shows that the implementation of KUR financing through the murabahah contract at Bank Syariah KC Pati Sudirman is in accordance with the DSN MUI Fatwa No. 04 / DSN-MUI / IV / 2000 concerning the Murabahah Contract, where the bank as a provider of funds then gives trust to customers to buy goods according to their wishes.